Penerapan sistem hazard analysis and critical control point (HACCP) pada sistem produksi gula tebu di Kabupaten Bombana - Dhian Herdhiansyah; Audhiyah Hayu Untari Punara Hayu Untari Punara; Sukmawati Abdullah; Asriani Asriani; Sarinah Sarinah (AGROINTEK, 2026)
The scarcity of data and oversight concerning the implementation of food safety systems presents significant challenges in ensuring the quality and safety of cane sugar products in Indonesia, particularly within Bombana Regency. The Hazard Analysis Critical Control Point (HACCP) system, a preventive strategy, has demonstrated efficacy in managing potential hazards throughout the food production chain. However, the extent to which the HACCP system has been effectively implemented in cane sugar processing companies in this region remains uncertain. This study seeks to evaluate the implementation of the Hazard Analysis and Critical Control Point (HACCP) system within cane sugar production systems in Bombana Regency. A descriptive methodology was employed, integrating both qualitative and quantitative techniques. Data were collected through structured observations utilizing an assessment sheet with a binary scoring system (1 = "Yes," 0 = "No") across five primary divisions: production, laboratory, milling, maintenance, and warehousing. The findings revealed that the average level of HACCP implementation was 71.19%, indicating a reasonably good execution of the system. Nonetheless, there remain critical areas requiring enhancement to achieve higher and more sustainable food safety standards.